The Role of Notch3 Signaling in Cancer Stemness and Chemoresistance: Molecular Mechanisms and Targeting Strategies - Xiu, Mengxi; Wang, Yongbo; Li, Baoli; Wang, Xifeng; Xiao, Fan; Chen, Shoulin; Zhang, Lieliang; Zhou, Bin; Hua, Fuzhou (Frontiers in Molecular Biosciences, 2021)
Aberrant Notch signaling profoundly affects cancer progression. Especially the Notch3 receptor was found to be dysregulated in cancer, where its expression is correlated with worse clinicopathological features and poor prognosis. The activation of Notch3 signaling is closely related to the activation of cancer stem cells (CSCs), a small subpopulation in cancer that is responsible for cancer progression. In addition, Notch3 signaling also contributes to tumor chemoresistance against several drugs, including doxorubicin, platinum, taxane, epidermal growth factor receptor (EGFR)–tyrosine kinase inhibitors (TKIs) and gemcitabine, through complex mechanisms. In this review, we mainly focus on discussing the molecular mechanisms by which Notch3 modulates cancer stemness and chemoresistance, as well as other cancer behaviors including metastasis and angiogenesis. What’s more, we propose potential treatment strategies to block Notch3 signaling, such as non-coding RNAs, antibodies and antibody-drug conjugates, providing a comprehensive reference for research on precise targeted cancer therapy.